The contribution of the left precuneus to emotion memory in migraine without aura patients - Li, Meiqin; Li, Xiaoshu; Zhu, Wanqiu; Zhu, Jiajia; Wang, Haibao; Gao, Ziwen; Wu, Xingqi; Zhou, Shanshan; Wang, Kai; Yu, Yongqiang (Frontiers in Neuroscience, 2022)
Background: The impact of migraine without aura (MWoA) on cognitive function remains controversial, especially given the sparse literature on emotional memory. Methods: Twenty-seven MWoA patients and 25 healthy controls (HCs) were enrolled in this cross-sectional study. Emotional memory behavior was evaluated by combining incidental encoding with intentional encoding of five emotional categories of visual stimulus (positive valence + high arousal (PH), negative valence + high arousal (NH), positive valence + low arousal (PL), negative valence + low arousal (NL) and neutral (N)). The recollection performance (Pr) was measured and compared. Then, the neural relevance was explored by correlating the Pr with gray matter volume (GMV) and resting-state functional connectivity (rs-FC) based on structural and functional magnetic resonance imaging. Results: Although no significant differences in recollection performance or emotional enhancement of memory effect were observed, MWoA patients were more sensitive to the valence and arousal of emotional stimuli under incidental encoding. Importantly, the Pr-PH under incidental encoding and Pr -PL under intentional encoding were negatively correlated with the GMV of the left precuneus, and the rs-FC between the left precuneus and putamen was positively correlated with Pr-PL under intentional encoding in MWoA patients. Conclusions: Our study demonstrated the tendency for influence of migraine on emotional memory and revealed the left precuneus as a critical contributor to the recollection performance, providing novel insights for understanding emotional memory and its neural mechanisms in MWoA patients.